Evaluation of Household Knowledge on Water Supply, Hygiene and Sanitation Practices in So-Ava District (South Benin) - Dan, Oswald F.; Ahouansou, D. Mathieu Maurice; Sintondji, Luc O.; Dossou-Yovo, Elliott R.; Amouzouvi, Dodji (European Scientific Journal, ESJ, 2018)
The adoption of good practices in access to water, hygiene and sanitation is very important for the well-being and socio-economic development of any community. The objective of the study was to evaluate the knowledge and practices that households adopt regarding water supply, hygiene and sanitation. For this, a survey was conducted among 386 households in the seven districts of the commune of Sô-Ava. The data collected was analyzed using the XLSTAT 17 software and the Excel Spreadsheet. The results obtained show that in the commune of Sô-Ava, drilling is the most used water source and that nearly 66.33% of households do not cover their containers during the transport of water with a rate that varies from 2.85 to 25.39% from one borough to another. Sô-Ava is the district that has the highest number of latrines is that with a rate of 3.11%. In addition, most households dispose of their garbage and wastewater either in the wild or in the water body in the absence of a waste collection system. The low level of hygiene and sanitation observed could affect the quality of drinking water and hence the health of the population.